Quality and Performance Evaluation of Jatropha Oil Blended with Kerosene for Cooking Stoves in Ethiopia - Adamu, Lake Belete; Adem, Kamil Dino (Journal of Renewable Energy, 2020)
In Ethiopia, the majority of rural household uses firewood with three-stone fire for cooking. Due to poor performance of the stove, there are major health issues created by indoor air pollution. To alleviate this problem, various efforts are undergoing such as the use of plant oil as an alternative fuel for cooking. This plant’s oils are available in the rural areas with minimal effort and water. In this study, Jatropha oil was blended with kerosene to present it as an alternative fuel for the rural poor in Ethiopia. The blends of varying proportions of Jatropha oil and kerosene were prepared, analyzed, and compared with the fuel properties of kerosene. The viscosity of Jatropha oil was reduced in ranges 86.3% to 4.5% by heating the oil from 30°C to 100°C. In order to understand the value of the blended fuel, the blended fuel was used for the evaluation of the performance of a stove for its thermal efficiency and indoor air pollution. Thermal efficiency of the newly designed bio-oil stove (Jatrok stove) was 52–66% with its specific fuel consumption ranging from 30 to 37 g/L and the fire power of the stove ranging from 1398 to 1433 watt using 10% to 40% Jatropha oil in the blend. In the case of emission, the Jatrok stove showed 11.5 to 9.5 grams of carbon monoxide (CO) and 352 to 289 grams of carbon dioxide (CO2) to boil 2.5 liters of water.The performance of the Jatrok stove using blended fuels was evaluated and compared with other domestic cooking stoves available in Ethiopia, making the stove comparable. A wider dissemination of such kind of plant oil blended with a kerosene-operated stove could reduce the environmental load in addition to lessoning the indoor air pollution in the kitchen.